The Effect of Dumbell Load Training on Straight Block Speed on Muay Thai Athletes Unsyiah Banda Aceh - Rahmat, Zikrur; Irfandi, Irfandi; Munzir, Munzir (Journal Coaching Education Sports, 2022)
Based on the results of observations at UKM Unsyiah, not all athletes from UKM Muay Thai Unsyiah can hit "straight" well and quickly. There are still many who make shots that are not directed, not on target, and weak on the targets they do hit. This situation is caused by the lack of support from the physical ability of the athlete and the lack of mastery of hitting techniques properly and correctly. In addition, it was found that around 80% of beginners experienced weakness when hitting straight, which was caused by weak weight training. The purpose of this study was to determine the effect of dumbbell weight training on the speed of straight strokes in the Unsyiah Muay Thai Student Activity Unit athletes. This research method uses quantitative research using a correlational technique design. The sample used was the UKM Muay Thai Unsyiah athletes, totaling eight people, consisting of four male athletes and four female athletes. The results showed that dumbbell weight training had an effect on the speed of straight strokes in the athletes of UKM Muay Thai Unsyiah. The results of this study mean that the better the straight stroke speed of an athlete, the better the results are obtained from dumbbell weight training.